Phenolics and flavonoids content determination and in-vitro antioxidant evaluation for radical scavenging activity of extracts from Dialium indum var. indum L. fruits - Osman, Muhamad Faris; Mohd Hassan, Norazian (2016)
Phenolic compounds are the largest group of phytochemicals, which have been studied to account for most plants antioxidant activity while flavonoids are the largest group of plants phenolics. High phenolics, flavonoids, saponins, and tannins content have been linked to the high antioxidant activity of plant extracts. Intake of plants with high phenolics content is linked with reduced risk for chronic disease. Dialium indum or black velvet tamarind is known by Malaysians and Indonesians as keranji which is sold at local markets as sweets. This study was conducted to investigate the total phenolics and flavonoids content and in-vitro DPPH radical scavenging activity of D. indum var. indum L. fruits. Samples (mesocarp, pericarp, and seed of fruits) were extracted by using cold maceration with distilled water heated to 40 °C for 1 hour and then frozen at -80 °C. All samples were then freeze-dried. For direct methanolic extract, all samples were cold macerated in methanol, filtered, then dried by using rotary evaporator at 40 °C. For consecutive organic solvents extraction, the same procedure for direct methanol extraction was used but all samples were cold macerated in n- hexane, dichloromethane, and methanol consecutively. The total phenolic (TPC) was determined using gallic acid standard curve while total flavonoid content (TFC) was determined using quercetin standard curve. Results were expressed as mg quercetin equivalence (QE) per gram of extract ± SEM. DPPH radical scavenging activity was employed to determine the percentage of inhibition of DPPH radical and IC50 were calculated. The results were compared with the standard ascorbic acid. Data were statistically analyzed using Analysis Toolpak, Microsoft Excel 2013. One-way analysis of variance (ANOVA) and Pearson correlation coefficient was determined and the significant difference was set at p < 0.05. Fractionated methanolic seed extract of the fruits contained highest amount of phenolics (93.51 mg GAE/g dry extract), followed by direct methanolic seed extract (59.95 mg GAE/g dry extract), and fractionated dichloromethane pericarp extract (43.26 mg GAE/g dry extract). Total flavonoids contents of the extracts showed that the fractionated dichloromethane pericarp extract had the highest amount of flavonoids (9.18 mg QE/g dry extract). A moderate positive correlation (r = 0.46) was obtained between total phenolics and total flavonoids content for all extracts tested. IC50 of fractionated dichloromethane pericarp extract was found to be 71.28 μg/mL while the standard ascorbic acid had IC50 of 1.44 μg/mL. There was significant difference (p < 0.05) in percent of DPPH radical inhibition at highest concentration tested (1000 μg/mL) between fractionated dichloromethane pericarp extract and the standard ascorbic acid. This study showed that the fractionated dichloromethane extract of D. indum var. indum L. fruit pericarp had positive results for flavonoids and DPPH radical scavenging activity. The results indicated that the flavonoids with antioxidant activity were semipolar in nature. This study acknowledged the in-vitro antioxidant properties of D. indum fruit pericarp; thus, indicated that this underutilized fruit has potential utilization in future natural products.